PENGARUH DISIPLIN GURU EKONOMI TERHADAP HASIL BELAJAR SISWA DI SMA PGRI 1 PONTIANAK - Apriadi, Bayu; Aminuyati, Aminuyati; Okianna, Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to determine the effect of the discipline of economic subject teachers on student learning outcomes in class X SMA PGRI 1 Pontianak academic year 2016/2017